2021
DOI: 10.3390/microorganisms9051027
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Oral, Vaginal, and Rectal Microbial Profiles during Pregnancy: A Pilot Study on the Bacterial Co-Residence in Pregnant Women

Abstract: Preterm birth (PTB) and threatened preterm labor (TPL), an important pre-PTB state, are major obstetric complications during pregnancy. However, their triggers have not been fully elucidated. The vagina is dominated by Lactobacillus species (categorized as community state types; CSTs I, II, III, and V) or by mixed anaerobes (CST IV). An abundance of the latter is associated with bacterial vaginosis (BV) and BV-triggered PTB/TPL. To identify factors that influence the diversity of vaginal microbiota associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
8
0
3
Order By: Relevance
“…We included the rectum, a body site that is not often sampled and observe that it shares many characteristics with faeces ( Jones et al , 2018 ; Fair et al , 2019 ), but it is also unique. The rectal microbiome has previously been suggested to be a reservoir of bacteria that can readily colonise the vagina ( Kostic et al , 2014 ; Fudaba et al , 2021 ). This is partially confirmed here in the observation that Lactobacillus strains found in the rectum are significantly more frequent in the vagina of the same individuals, as previously reported ( Antonio et al , 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…We included the rectum, a body site that is not often sampled and observe that it shares many characteristics with faeces ( Jones et al , 2018 ; Fair et al , 2019 ), but it is also unique. The rectal microbiome has previously been suggested to be a reservoir of bacteria that can readily colonise the vagina ( Kostic et al , 2014 ; Fudaba et al , 2021 ). This is partially confirmed here in the observation that Lactobacillus strains found in the rectum are significantly more frequent in the vagina of the same individuals, as previously reported ( Antonio et al , 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, 63 bacterial species were identified in the vagina or rectum, 44% of which were found in both organs, and the genotypes of 68% of the species were identical ( 56 ). A recent study showed that BV-associated bacteria in the vagina and rectum in pregnant women were individually detected by species-level Spearman correlation coefficient analysis ( 57 ). Furthermore, orally administered probiotic strains were also detected in the vagina ( 58 61 ).…”
Section: Vagina-gut Axismentioning
confidence: 99%
“…O acúmulo de ácido láctico acidifica o ambiente vaginal a um pH ideal (pH < 4,5) que atua impedindo o crescimento e a colonização de outras espécies patogênicas, tanto bacterianas (como ocorre com a VB) quanto fúngicas. Além disso, o ácido láctico demonstrou inativar o HIV, o que pode explicar as observações de que a transmissão do HIV pode ser diminuída em indivíduos com uma comunidade vaginal dominada por espécies de Lactobacillus (CHU, et al, 2018;FUDABA, et al, 2021).…”
Section: Vaginose Bacterianaunclassified
“…O microbioma vaginal normal difere de acordo com a etnia. Várias análises de perfis microbianos vaginais humanos, incluindo um estudo racial comparativo em larga escala foram realizadas, em que as espécies foram correlacionadas com o PP em afro-americanos, enquanto L. crispatus foi negativamente correlacionado com o PP (FUDABA, et al, 2021).…”
Section: Essas Aminas Produzem O Clássico Odor De Peixe Característic...unclassified